CONDITIONS OF A SINGLE INTAKE DESCENDING OF INTERMEDIATE CASING STRINGS OF AN EXCESSIVE WEIGHT COMPARED TO A DERRICK LOAD CAPACITY - Soloviov, V. V.; Mykhailovska, O. V.; Yermakova, I. A. (Academic journal Industrial Machine Building Civil Engineering, 2018)
The way of the intermediate casing string descending is considered. It allows overcoming the limits of derrick load capacity through the weight transferring descending intermediate casing string on the cemented string that is based on the foundation. In particular, technology is developed where the weight of each additional string, as it builds-up, is equivalent to additional friction forces which arise in the enlarged area. Such a descent technology does not depend on the load capacity of the derrick load capacity, does not create loads on the basis of derricks as well as additional tensile loads in the string with an increase in its length. It is proved that if such a condition is met, all known restrictions for the descent of intermediate columns of any length in a single intake are removed. Authors determined descending casing string weight that is distributed over the previously installed and cemented string. It is suggested to distribute casing string weight on existing and cemented string.